2022
DOI: 10.3390/children9070958
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Views with Music Therapy in the Pediatric Intensive Care Unit: A Retrospective Cohort Study

Abstract: Purpose: Music therapy intervention (MT) could be used as an adjunctive therapy in PICU for anxiety and pain management. The aim of the study was to examine the perception of MT by children’s parents in a PICU of a tertiary care teaching hospital. Methods: This is a retrospective cohort study summarizing the results of an institutional quality improvement initiative. Questionnaires were distributed to parents whose children were exposed to MT. Results: From April 2019 to July 2021, 263 patients received a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…3 4 The majority of parents thought that music therapy helped their child to communicate (89%), feel less isolated (100%) cope with stress during hospitalization (100%), contributed to physical recovery (90%), and alleviated feelings of anxiety (90%). 5 A meta-analysis showed that music intervention significantly decreased the pain levels, both in the newborn group and in the infant/children group. Music intervention significantly reduced heart rate and respiratory rate and increased peripheral capillary oxygen saturation.…”
mentioning
confidence: 99%
“…3 4 The majority of parents thought that music therapy helped their child to communicate (89%), feel less isolated (100%) cope with stress during hospitalization (100%), contributed to physical recovery (90%), and alleviated feelings of anxiety (90%). 5 A meta-analysis showed that music intervention significantly decreased the pain levels, both in the newborn group and in the infant/children group. Music intervention significantly reduced heart rate and respiratory rate and increased peripheral capillary oxygen saturation.…”
mentioning
confidence: 99%
“…The presence of a parent; interventions such as art therapy, music therapy, sports therapy, and physiotherapy; and visits from the psychosocial service, the hospital school, and clinic clowns can promote psychological health during hospital treatment [18][19][20][21]. Music therapy, a clinical and evidence-based use of music interventions to accomplish individualized aims within a therapeutic relationship [22], can be used to promote children's and parents' psychological wellbeing during their hospitalization [23]. This kind of non-drug intervention is effective in reducing pain and anxiety [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Music therapy, a clinical and evidence-based use of music interventions to accomplish individualized aims within a therapeutic relationship [22], can be used to promote children's and parents' psychological wellbeing during their hospitalization [23]. This kind of non-drug intervention is effective in reducing pain and anxiety [23][24][25][26]. Live music therapy has a stabilizing effect on the vital signs of heart rate, oxygen saturation [27], and respiratory rate and blood pressure [28].…”
Section: Introductionmentioning
confidence: 99%
“…Das individuelle und improvisierte Musizieren dient als nonverbale Form der Kommunikation [6] zur Erreichung individueller Ziele. Es wird auf die körperlichen, emotionalen, kognitiven und sozialen Bedürfnisse der Patient*innen eingegangen [7] und fördert das Wohlbefinden während eines Klinikaufenthaltes [8].…”
Section: Hintergrundunclassified